2016
DOI: 10.1039/c6gc01523a
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic and mechanistic insights into the production of ethyl levulinate from biorenewable feedstocks

Abstract: The importance of ethyl levulinate (EL) as a fuel additive and a potential biomassderived platform molecule is noteworthy. EL is obtained from the esterification of levulinic acid (LA) in presence of ethanol. Besides LA, the acid-catalyzed ethanolysis reaction to produce EL is carried out on a variety of biomass-derived substrates which include; furfuryl alcohol (FAL), chloromethyl furfural, monosaccharides, polysaccharides and lignocellulosic biomass. The acid catalysts employed for such conversions covers a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
118
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(121 citation statements)
references
References 168 publications
1
118
0
2
Order By: Relevance
“…A variety of substances were detected after the reaction, namely glucose, fructose, ethyl glucoside (EGO), ethyl fructoside (EFO), HMF, EMF, and ethyl levulinate (EL). Factually, ethyl formate can also be generated along with EL in a serial mode from the reaction of the furan derivatives and ethanol [26][27][28]. However, ethyl formate was not observed in our tests, probably due to no separation of ethyl formate and solvent ethanol for the equipped GC instrument.…”
Section: Conversion Of Fructose In Ethanol Medium Over Various Metalmentioning
confidence: 45%
“…A variety of substances were detected after the reaction, namely glucose, fructose, ethyl glucoside (EGO), ethyl fructoside (EFO), HMF, EMF, and ethyl levulinate (EL). Factually, ethyl formate can also be generated along with EL in a serial mode from the reaction of the furan derivatives and ethanol [26][27][28]. However, ethyl formate was not observed in our tests, probably due to no separation of ethyl formate and solvent ethanol for the equipped GC instrument.…”
Section: Conversion Of Fructose In Ethanol Medium Over Various Metalmentioning
confidence: 45%
“…In recent years, research on the transformation of furfuryl alcohol to levulinate esters has been reported at an increasing rate [13][14][15]. Acid catalyst is identified as the key point for the synthesis of levulinate esters, and is thus the focus of the study.…”
Section: Introductionmentioning
confidence: 99%
“…[57] Thep athways to such tailor-made biofuels or related valueadded chemicals [248][249][250][251][252] must satisfy the principles of "Green Chemistry" [253] to address the criteria of sustainability on the basis of the feedstock as well as in the production process. [254][255][256] In this context, the selective conversion of the raw materials into the desired products,while largely maintaining the synthetic effort of nature,a ppears to be an attractive approach.…”
Section: The Concept Of Target-oriented Pathway Designmentioning
confidence: 99%